The Implementation of Principal’s Leadership in Improving Teacher’s Professionalism - Sartina, Yuyun; Ahyani, Nur; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze how the principal’s leadership is implemented and find out the obstacles faced in increasing teacher professionalism at SDN 123 Palembang. The research method used is a qualitative method that captures information from natural conditions in an object’s life that is associated with a problem, both theoretically and practically. This study’s process included data collection and compilation, as well as data analysis and interpretation. The study’s findings indicate that teachers play an important role in preparing potential human resources. As a result, teachers must take an active role and position themselves as professionals to meet the demands of the times. In this case, the teacher serves as an educator and mentor, providing direction and demanding that students learn rather than simply transferring knowledge. The teacher’s educational background is a supporting factor, as all teachers at SDN 123 are undergraduate graduates, and some of them are community leaders in their neighborhood, while the inhibiting factor is a lack of teaching facilities.